69.0k views
0 votes
Show that cos(3theta) = 4cos3(theta) − 3cos (theta).

User Nunser
by
4.8k points

1 Answer

6 votes

Explanation:

To prove:


\cos 3\theta=3\cos^3 \theta-3\sin^2 \theta\cos \theta

Identities used:


\cos(A+B)=\cos A\cos B+\sin A\sin B ......(1)


\sin 2A=2\sin A\cos A ........(2)


\cos 2A=\cos^2A-\sin^2 A .......(3)


\sin^2A+\cos^2A=1 .......(4)

Taking the LHS:


\Rightarrow \cos 3\theta=\cos (\theta +2\theta )

Using identity 1:


\Rightarrow \cos (\theta +2\theta )=\cos \theta \cos 2\theta-\sin \theta \sin 2\theta

Using identities 2 and 3:


\Rightarrow \cos \theta (\cos ^2\theta-\sin^2 \theta )-\sin \theta (2\sin \theta \cos \theta )\\\\\Rightarrow \cos^3\theta -\sin^2\theta \cos \theta -2\sin^2 \theta \cos \theta \\\\\Rightarrow \cos^3\theta -3\sin^2\theta \cos \theta

Using identity 4:


\Rightarrow \cos^3\theta -3(1-\cos^2\theta) \cos \theta\\\\\Rightarrow \cos^3\theta-3\cos \theta+3\cos^3\theta\\\\\Rightarrow 4\cos^3\theta -3\cos \theta

As, LHS = RHS

Hence proved

User Picolino
by
4.9k points